Determinação e limitação dos esforços no transporte por empuxo humano Determination and limitation of efforts in transportation by human pushing - Manoel Godinho de Amorim Neto (Universidade de São Paulo, 1986)
As normas estabelecem como limites de levantamento de peso 40 e 60 kg, sem auxílio de equipamento. Não havendo limites para o ato de empurrar, foi feito estudo com o objetivo de mostrar como levantar a indeterminação desses esforços, e provar que os mesmos costumam ser bem superiores à capacidade de trabalho do organismo do homem. Essa capacidade varia, conforme foi concluído, de 10,5 kgm/seg e 100 kgm/seg, segundo o tempo de aplicação, seja de 8 horas ou de 4 segundos. Technical standards require that the lifting and transportation of weights by workers without equipment be limited to between 40 and 60 kilograms. However, there are no limits for the act of pushing. This work shows how to find the unknown values of such acts and prove that they are frequently well above the working capacity of the human body. This ability varies from 10.5 kgm/s to 100 kgm/s, according as if the effort is exerted during 8 hours or 4 seconds, respectively, as shown at the end of this paper.